Cardiac autonomic control during non‐REM and REM sleep stages in paediatric patients with Prader‐Willi syndrome. (18th August 2020) - Brito, Leandro C.; Queiroga, Thereza; Franco, Ruth R.; Passone, Caroline G. B.; Lopes, Maria‐Cecilia; Shea, Steven A.; Bueno, Clarissa; Soster, Leticia M. S. F. A.
Abstract: Cardiac death is the second most prevalent cause in Prader‐Willi syndrome (PWS). Paediatric patients with PWS often present cardiac autonomic dysfunction during wakefulness, obesity and sleep‐disordered breathing. However, the extent of cardiac autonomic modulation during sleep in PWS has not been documented. The objective of this study was to assess alterations in cardiac autonomic modulation of paediatric patients with PWS during different sleep stages. Thirty‐nine participants in three groups: 14 PWS, 13 sex and age‐matched lean controls (LG) and 12 obese‐matched controls (OB). All participants underwent overnight polysomnography, including continuous electrocardiogram recordings. Heart rate variability (HRV) was analysed during representative periods of each sleep stage through time and frequency domains calculated across 5‐min periods. Between‐within ANOVAs were employed ( p  < .05). The results show that total HRV was lower in PWS than OB and LG during slow‐wave sleep (SWS) (standard deviation of all NN intervals [SDNN] ms, p  = .006). Parasympathetic modulation assessed by time‐domain analysis was lower during SWS in PWS compared to both OB and LG (square root of the mean of the sum of the squares of differences between adjacent NN intervals [RMSSD] ms, p  = .004; SDSD, standard deviation of differences between adjacent NN intervals [SDSD] ms, p  = .02; number of adjacent NN intervals differing by >50 ms [NN50] ms, p  = .03; proportion of adjacent NN intervals differing by >50 ms [pNN50] ms, p  = .01). Sympathovagal balance assessed by frequency‐domain analysis was lower during both N2 and SWS than during the rapid eye movement (REM) sleep stage, but not different among groups. In conclusion, this group of paediatric patients with PWS had impaired cardiac autonomic balance due to reduced parasympathetic modulation during SWS. This result could imply an underlying increased cardiovascular risk in PWS even during early age and independent of obesity.